Exploring the practical wisdom of mētis for management learning. Issue 4 (September 2014) - Mackay, David; Zundel, Mike; Alkirwi, Mazin
This article investigates the nature of practical wisdom in organizational life through the notion of mētis, which we interpret as situated resourcefulness. Drawing on Greek mythology, we explore the nature of mētis and discuss its mythological characteristics in relation to a contemporary organizational episode. We suggest that the consideration of mētis not only highlights the shortcomings of measurement and conceptual order in management, but also allows us to project a more processual managerial response which accepts the fallacy of unilateral control and strives towards a harmonic balance of continually unfolding, dynamic and recursive patterns.